Immune status of patients with acne and concomitant skin malasseziosis - Koretskaya, E. Yu. (Pathologia, 2014)
Introduction: Acne is the most common skin disease that affects up to 85% of people between 12 and 25 years old and 11% of persons over the age of 25 years. Frequently the disease acquires a severe course, which significantly reduces the quality of life indicators. Etiopathogenesis of acne has a multifactorial nature, the leading role is given to shifts in the immune status. Aim of the research: To evaluate the state of the immune status in patients with acne and concomitant skin malasseziosis. Materials and methods: 120 patients with acne were observed: 35 (45.8%) men and 65 (54.2%) women, aged 16-27 years. Duration of the disease was mostly 3-8 years (80.8%). Papulopustular acne was diagnosed in 102 patients, nodulocystic – in 18 ones. Skin malasseziosis was found in 100 patients in the form of pityriasisversicolor, purulent folliculitis, Darier’s disease (keratosis follicularis), and scalp pityriasis. Study of leukocyte count, leukocyte phenotyping and the study of phagocytes function were carried out. Furthermore, levels of IgA, IgG, IgM and concentration of IL-10 and IL-12 were studied in the peripheral blood. Results: We observed the statistically significant decrease in Phagocytic Index and Phagocytic Number, more demonstrative in patients with concomitant malasseziosis. We also noted the decrease of NBT-test indicators, more demonstrative in patients with the infection. The most pronounced inhibition of phagocytic activity was observed in patients with more severe acne (stage IV). In the study of number of lymphocytes populations and subpopulations in patients with acne violations of immunoregulatory type were identified: dissociation of CD3+ and CD22+, CD4+, CD8+, and especially CD16+ level, which led to the depression of T-cell-mediated immunity, which were more pronounced in patients with acne and concomitamtmalasseziosis, especially in patients with stage IV dermatosis. In the study of immunoglobulin levels an increase of IgM and IgG was marked, especially in patients with concomitant malasseziosis, which depended on the stage and form of dermatosis. We consider this fact as the progredient progression of acne with the presence of immunopathological changes under the influence of concomitant Malassezia infection. We observed the significant increase in production of IL-10 and IL-12 in patients with acne, which indicates the hyperactivity of anti-inflammatory mechanisms and may be the background for the intensification of microorganisms’ colonization, which was confirmed by the significantly higher indicators of these cytokines levels in patients with acne and concomitant skin malasseziosis.